The Scaffolding Used by the 6 Grade English Teacher in Online Learning Situation (Universitas Negeri Semarang, 2022)
This study aims to examine the CLIL (Content and Language Integrated Learning) 6 Grade English teacher’s scaffolding in online learning and the problems faced by the CLIL (Content and Language Integrated Learning) 6 Grade English teacher in online learning situation. The research questions in this research are “How is the scaffolding used by CLIL 6 Grade English teacher in online learning situation?” and “What are the problems faced by the CLIL 6 Grade English teacher in online learning situation?”. This study was done on November 18th and 25th 2021 in one of the schools in Tangerang. The data were gathered from one English teacher and 78 grade 6 students using classroom observation, document analysis and interview. The results show that there are a number of types of scaffolding found in the learning process. The teacher also implemented good learning media in the online learning process. The problems faced by the 6 Grade English teacher in online learning situation are related to the use of the learning media, the students’ engagement to the learning process, the amount of the students, and the insufficient amount of time given for the teacher in the meeting.